Silica and zirconia supported tungsten, molybdenum and gallium oxide catalysts for the synthesis of furfural - Bhaumik, Prasenjit; Kane, Tanushree; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2014)
SiO2 and ZrO2 supported W, Mo and Ga oxide catalysts were prepared by a sol-gel and wet-impregnation method. The 10 wt% WO3/SiO2 (sol-gel) catalyst showed 61 +/- 2% furfural yield from hemicellulose in a one-pot fashion for at least 8 cycles. Based on XRD, TPD and Hammett acidity characterizations, the catalyst structure-activity correlation was drawn.

Solid base supported metal catalysts for the oxidation and hydrogenation of sugars - Tathod, Anup; Kane, Tanushree; Sanil, E. S.; Dhepe, Paresh Laxmikant (Journal of Molecular Catalysis A-Chemical, 2014)
Pt impregnated on gamma-Al2O3 (acidic support) and hydrotalcite (basic support) catalysts were synthesized, characterized and used in the oxidation and hydrogenation reactions of C5 and C6 sugars. In the absence of homogeneous base, 83% yield for gluconic acid; an oxidation product of glucose can be achieved over Pt/hydrotalcite (HT) catalyst at 50 degrees C under atmospheric oxygen pressure. Similarly, 57% yield for xylonic acid, an oxidation product of xylose is also possible over Pt/HT catalyst. Hydrogenation of glucose conducted using Pt/gamma-Al2O3 + HT catalytic system showed 68% sugar alcohols (sorbitol + mannitol) formation. The 82% yield for C5 sugar alcohols (xylitol + arabitol) was obtained by subjecting xylose to hydrogenation over Pt/gamma-Al2O3 + HT at 60 degrees C. UV analysis helped to establish the fact that under alkaline conditions sugars prefer to remain in open chain form in the solution and thus exposes -CHO group which further undergoes oxidation and hydrogenation reactions to yield acids and alcohols. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Oxidation; Solid base; Sugars; Supported metal catalysts

Value addition to lignocellulosics and biomass-derived sugars: an insight into solid acid-based catalytic methods - Bhaumik, Prasenjit; Deepa, Ayillath K.; Kane, Tanushree; Dhepe, Paresh Laxmikant (Journal of Chemical Sciences, 2014)
For the synthesis of important platform chemicals such as sugars (xylose and arabinose) and furans (furfural and 5-hydroxymethylfurfural (HMF)) from carbohydrates (hemicellulose and fructose) solid acid catalysts are employed. Similarly, over solid acid catalysts, conversion of lignin into aromatic monomers is performed. It is observed that in the dehydration of fructose, because of higher hydrothermal stability, silicoaluminophosphate (SAPO) catalysts give better activity (78% HMF yield) compared with other solid acid catalysts (<63% HMF yield) at 175 degrees C. Particularly, SAPO-44 catalyst can be reused at least 5 times with marginal decrease in the activity. Zeolite, BUSY (Si/Al = 15) is active in the conversion of isolated (pure) hemicellulose to produce 41% C-5 sugars in water. The catalyst is also active in the selective conversion of hemicellulose from bagasse to yield 59% C-5 sugars. It is possible to obtain high yields of furfural (54%) directly from bagasse if instead of water, Water+toluene solvent system is used. Depolymerization of lignin using HUSY catalyst produced aromatic monomers with 60% yield at 250 degrees C. A detailed catalyst characterization study is performed to understand the correlation between catalyst activity and morphology. To understand the effect of impurities present in the substrate over solid acid catalysts, metal-exchange study is carried out.
Keywords: aromatic monomers; Biomass; furans; Hemicellulose; lignin; solid acid catalyst